KETERKAITAN PAHAM DEMOKRASI TERHADAP SISTEM HUKUM INDONESIA SETELAH PERUBAHAN UNDANG-UNDANG DASAR 1945 - Yunita Syofyan; Delfina Gusman; Alsyam Alsyam (UNES Law Review, 2022)
After the Amendment of 1945 Constitution, democracy and Rule of Law become two concepts. They are the concept on how to run the power and run the goverment of Indonesia. Both concept, are interconected among each others and can not be separated, because on one side, democracy gives the grounds and mechanisme of power based on the principles of togetherness and equality, while on the other side, rule of law gives guide lines that goverment in the state is not a human but the law of human being. The both of concepts have relation each other. This article are trying to connected and related both concepts in an unseperated function.